2019
DOI: 10.1158/1055-9965.epi-18-1066
|View full text |Cite
|
Sign up to set email alerts
|

A High Monocyte-to-Lymphocyte Ratio Predicts Poor Prognosis in Patients with Advanced Gallbladder Cancer Receiving Chemotherapy

Abstract: Background: Monocyte-to-lymphocyte ratio (MLR), neutrophil-to-lymphocyte ratio (NLR), and platelet-tolymphocyte ratio (PLR) have been reported to be prognostic markers in various cancers. However, the prognostic value of these inflammatory biomarkers, particularly MLR, in gallbladder cancer remains to be determined. Methods: From 2005 to 2016, 178 patients with histologically confirmed gallbladder adenocarcinoma who underwent palliative chemotherapy were queried in this study. The association between survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…The results above strongly suggest that stromal NNMT plays an important role in the progression of CRC. With the exception of a recent study in ovarian cancer, previous studies have not clarified the relationship between stromal NNMT expression and progression of cancer patients. With a cut‐off value of 106 for the IHC‐score of stromal NNMT, we classified 967 CRC patients into two subgroups with high or low stromal NNMT tumors.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The results above strongly suggest that stromal NNMT plays an important role in the progression of CRC. With the exception of a recent study in ovarian cancer, previous studies have not clarified the relationship between stromal NNMT expression and progression of cancer patients. With a cut‐off value of 106 for the IHC‐score of stromal NNMT, we classified 967 CRC patients into two subgroups with high or low stromal NNMT tumors.…”
Section: Discussionmentioning
confidence: 92%
“…The Maxstat package was used to identify the optimal cut-off value of the IHC score to define risk subgroups. 21 The Kaplan-Meier curves were used to estimate the DSS and DFS, and the survival curves was compared by the log-rank test. The hazard ratios (HRs) and corresponding 95% confidence intervals (CIs) were estimated by Cox proportional hazards models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence implies that inflammation acts an absolutely required part in the formation of neoplasm possibly via all kinds of transcription factors, chemokines, as well as cytokines [10,11]. In many published knowledges, the roles of inflammatory factors like neutrophil-to-lymphocyte ratio (NLR) [48], monocyte-to-lymphocyte ratio (MLR) [49], and C-reactive protein (CRP) [50] have always been delineated in patients who suffered from cancer. Given that, we turned our attention on the association between another inflammatory immune factors, platelet-to-lymphocyte ratio (PLR), and gynecological cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various serum markers, including the leukocyte differentials and neutrophil/lymphocyte ratio (NLR) have been evaluated as surrogate markers for predictive and prognostic values in various entities, such as rheumatoid arthritis, pancreatitis, and several malignancies [10][11][12][13]. Recent research focusing on cost-effective biomarkers in IBD has reinvigorated the examination of white blood cell patterns, and a few studies have showed the potential of neutrophil and lymphocyte counts and their ratio to assess the disease activity either in UC or CD [14,15].…”
Section: Introductionmentioning
confidence: 99%